Estrutura eletrônica de sistemas triangulares de carbono e nitreto de boro - Terroso, Carolina Jordoni (2024)
Triangular carbon systems in single monolayer, also known as n-triangulenes (where n is the number of carbon rings at the base of the triangle), hold significant potential in nanoelectronics and spintronics applications due to their electronic structure and ground state multiplicity being dependent on the system’s size. However, controlling their high chemical reactivity at the edges, due to its zig-zag edge configuration, remains a challenge from an experimental standpoint. The strategy investigated in this study to address this characteristic is to create an insulating matrix of hexagonal boron nitride (h-BN) so that the triangulenes can be embedded in the h-BN structure, maintaining their electronic and magnetic properties. Given the size of the studied systems, the Density Functional Theory will be used in all electronic structure calculations. The results revealed that the formation of h-BN or carbon domains is equally possible, and the multiplicities of the ground state are determined solely by the carbon sites, regardless of their position, size, or whether the carbon islands are connected or not. Additionally, Lieb’s Theorem holds true in all cases when considering only the carbon sites, which can be a useful tool in determining the ground state spin of these systems